2020
DOI: 10.15408/etk.v19i1.11264
|View full text |Cite
|
Sign up to set email alerts
|

Transformational Leadership Style and Talent Retention in Pakistani Banks: A Serial Multiple Mediation Model

Abstract: The objective of this research was to determine factors that mediate between transformational leadership style and retention of employees, as talent retention is an emerging issue for organizations due to workplace diversity. This study provides a guideline to the supervisors and leaders in managing their workforce. By using structural equation modeling (SEM), the result exhibited a positive impact between transformational leadership and talent retention, transformational leadership and job satisfaction, trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…Other studies, however, found that TL has no significant influence on employee turnover (Long et al, 2012). Inspirational motivation, for example, was found to have no impact on talent retention (Mir, Khan & Abbas, 2020).…”
Section: Statement Of Problemmentioning
confidence: 96%
See 1 more Smart Citation
“…Other studies, however, found that TL has no significant influence on employee turnover (Long et al, 2012). Inspirational motivation, for example, was found to have no impact on talent retention (Mir, Khan & Abbas, 2020).…”
Section: Statement Of Problemmentioning
confidence: 96%
“…Despite positive accolades associated with TL such as impact on job retention, team and individual performance (Abouraia & Othman, 2017;Braun, Weisweiler & Frey, 2013;Choi, Goh, Hisyam & Tan, 2016;McCallaghan, Leon, Jackson & Heyns, 2019), and predicting managers' performance (Nyokabi, K'Aol & Njenga, 2017), it has also been found to that some dimensions of TL have no significant impact on talent management. Long, Thean, Ismail and Jusoh (2012), for example, found that TL has insignificant influence on employee turnover, while Mir, Khan and Abbas (2020) noted that inspirational motivation has no impact on talent retention. Similarly, Ghadi, Fernando and Caputi (2013) found that TL influence on employee engagement was mediated by employee perception of work meaning.…”
Section: Introductionmentioning
confidence: 99%
“…According to Mondiani (2012), transformational leadership, namely the incorporation of charismatic leadership, is anticipated to boost employee performance. According to the findings of Al-Amin (2017) and Mir et al (2020), there is a significant and favorable correlation between transformative leadership and performance factors. Chen et al, (2018) provided @ @ @ different results, and Eliyana et al, (2019) showed that transformative leadership had no impact on employee performance.…”
Section: Introductionmentioning
confidence: 98%
“…Because it encourages staff participation and buy-in, transformational leadership can play a significant part in boosting overall worker productivity (Mir et al, 2020). According to Amin (2017), transformational leadership has the potential to raise the degree of employee engagement in the workplace.…”
Section: Introductionmentioning
confidence: 99%
“…Jurnal Ilmiah Administrasi Bisnis dan Inovasi mementingkan organisasi atau tim daripada kepentingan diri sendiri, dan (3) mengaktifkan kebutuhan-kebutuhan mereka pada yang lebih tinggi (Mir, et al, 2020;Dung & Hai, 2020).…”
unclassified